Efeitos do diagnóstico precoce da surdez nos processos de escolarização de alunos surdos - Camatti, Liane (2017)
The investigation carried out in this Thesis aims to understand the way in which the early diagnosis of hearing loss has functioned in the articulation of regulatory techniques with effects on both the constitution of deaf subjects and their schooling processes. It makes sense to question the practice of diagnosis in a doctoral course in Education in search for elements to help us understand important changes that have been noticed in scenarios and subjects in Deaf Education. Firstly, legal documents, programs and projects establishing current public policies that address linguistic, pedagogical or clinical issues related to deaf people in their schooling process were analyzed. Secondly, five early-diagnosed deaf children attending regular or deaf schools in 2016 were selected. By means of observations of those children in school contexts and interviews with their relatives, teachers and health professionals, we attempted to understand the effects of mechanisms put into operation by the policies analyzed. Due to the pertinence of Michel Foucault’s philosophical perspective, regarding the approach of Foucauldian Studies in Education, the analytical tools of norm and bio-politics were chosen for us to carry out the analysis. The study has enabled us to see how the current public policies positively invest in the lives, language and schooling processes of the deaf. In the sphere of life, quantification, evaluation, intervention and optimization techniques are put into operation, thus exerting power both on the body, considering the individual, and on the collectivity, on the deaf portion of the population. Concerning languages, they are in the center of actions directed to deaf people and, hence, they end up becoming strategic to the function of prescribing ways of being deaf. Finally, regarding schooling, regulation processes of all kinds are performed by the school institution, given its potential to shape conducts that fit the context. From the discussions about the functioning of auditory health programs and the analyses of the chain of utterances about the five deaf children under study, we discussed the way that the diagnosis has gone beyond the group of examinations and evidences that determine deafness and has become a bio-political practice. Its management field extends throughout the subjects’ lives, thus putting them in a permanent state of regulation by producing minor undetermined abnormal conditions that correlatively generate investment demands. Considering what the study has evidenced, we advocate the following thesis: the early diagnosis of hearing loss regulates the constitution of deaf subjects as well as their schooling processes, since it works as a broadened bio-political life management practice that permanently produces diagnosable abnormal conditions to which intervention actions are applied.